Study of moisture-induced temperature evolution in an engineered barrier system for a HLW repository - Manish Kumar Jha; Amit Jaiswal; A.K. Verma; Trilok Nath Singh (Results in Earth Sciences)
The present paper aims to assess the thermal behaviour of bentonite compaction's engineered barrier system (EBS) to designated dry density. An experiment was carried out on a small (centimetre scale) physical model of the EBS based on the design of the nuclear waste repository proposed by different studies. Temperature distribution within the physical model of the engineered barrier system has been recorded. Investigation of temperature evolution has been conducted in compacted bentonite at three different moisture contents: 10 %, 20 %, and 30 %. The temperature profile was recorded in the radial and lateral directions around the cylindrical heater with different moisture contents. A numerical model has also been developed to assess temperature evolution in radial and longitudinal directions at different moisture content in compacted bentonite. In the radial direction, the maximum temperature in the physical model at monitoring points reaches up to 71 °C 78°C and 79°C for moisture content of 10 %, 20 % and 30 %, respectively. Numerical simulation of the 3-dimensional model gives the maximum temperature of 61 °C, 68.6°C and 69.1°C, respectively, at a 10 %, 20 % and 30 % moisture level. Experimental results show that the maximum temperature developed in the longitudinal direction reaches up to 47°C, 53°C, and 56°C at monitoring points within bentonite having a moisture content of 10 %, 20 %, and 30 %, respectively. Temperatures obtained at a similar point through numerical simulation are 43°C, 47°C, and 53°C for moisture content of 10 %, 20 %, and 30 %, respectively. The difference between numerical and physical models varies up to 13 %. The study shows that the variation in moisture content significantly influences the temperature developed in the experimental setup of compacted bentonite.